2009
DOI: 10.2527/jas.2008-1120
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary glycyl-glutamine on growth performance, small intestinal integrity, and immune responses of weaning piglets challenged with lipopolysaccharide1

Abstract: The objectives of this study were to determine the effects of dietary glycyl-glutamine (Gly-Gln) on postweaning growth, small intestinal morphology, and immune response of stressed or nonstressed piglets. Pigs (n = 144; initially 4.49 kg and 14 d of age) were randomly allocated to 24 pens (6 pigs/pen) in an environmentally controlled nursery and assigned to Escherichia coli lipopolysaccharide (LPS) challenge (PBS vs. LPS) and Gly-Gln supplementation (0 vs. 0.15%) in a 2 x 2 factorial arrangement of treatments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
44
2
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 30 publications
5
44
2
2
Order By: Relevance
“…These results are in line with another study (YI et al, 2005), in which there was no effect of treatment throughout the overall experimental period. In contrast to our findings, some studies demonstrated that dietary supplementation with GLN or glycyl-GLN dipeptide improved growth performance in the first week after weaning in piglets challenged with E. coli K88+ or LPS (YI et al, 2005;JIANG et al, 2009). These results suggest that at an older age (28 days post-weaning) these effects might be overshadowed by normal physiologic growth.…”
Section: Resultscontrasting
confidence: 55%
See 1 more Smart Citation
“…These results are in line with another study (YI et al, 2005), in which there was no effect of treatment throughout the overall experimental period. In contrast to our findings, some studies demonstrated that dietary supplementation with GLN or glycyl-GLN dipeptide improved growth performance in the first week after weaning in piglets challenged with E. coli K88+ or LPS (YI et al, 2005;JIANG et al, 2009). These results suggest that at an older age (28 days post-weaning) these effects might be overshadowed by normal physiologic growth.…”
Section: Resultscontrasting
confidence: 55%
“…However, it is noteworthy to mention that the level of 0.3 µg of LPS used in the present experiment is much lower than the level used by other authors e.g. 200 µg kg -1 body weight of LPS in Jiang et al (2009). In a previous study, Lozano et al (2014) showed that challenging weaned pigs with 0.3 μg of LPS per pig per day did not promote any moderate or transient cortisol alterations.…”
Section: Resultsmentioning
confidence: 75%
“…Early weaning results in a sudden cessation of passive immunity from the milk of sows, when the immune system of piglets is still immature, making them vulnerable to diseases such as diarrhea (Ushida et al, 2008). Dietary supplementation with specific nutrients or immunomodulators could improve the performance and health of weaning piglets (Jiang et al, 2009). Cytokines are small peptides that play important roles in the regulation of immune and inflammatory responses (Pié et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have indicated that immunological stress can cause damage to the intestinal barrier structure and function (Dickinson et al 1999;Ding et al 2004;Jiang et al 2009). Nutritional regulation of the immune status through feed additives may have beneficial effects and provide a simple way of improving poultry health.…”
mentioning
confidence: 99%